EL MARKETING COMO HERRAMIENTA DE GESTIÓN EN LO PROFESIONAL Y PERSONAL - Mayurí Barrón, Jorge Vicente (2010)
Today more than ever, the globalization of markets, produces continuous changes in choices and preferences by consumers. These changes cause changes in supply and demand, making everyday the competitive pressure to be more intense, so that the marketing specialist of today, must work with a marketing model, that allows him at the end of a qualified and continuous process to achieve the targets of the company. The above mentioned model starts previous to a market research, identifying the culture and needs of consumers of the target market with the purpose of developing satisfiers from those needs, so that through a market segmentation and a study of consumer behavior, we can have the information that will allow the sales area to place the product with the best advantages in the market to achieve the customer loyalty. In a parallel way it is important to determine the marketing strategies that allow a better positioning through marketing variables, price, product, communication and distribution for the improvement of the marketing plan, to achieve an efficient management of the Operational marketing which is the cornerstone of strategic marketing.